BIOPOLYMERS APPLIED TO REMOVE METAL IONS THROUGH ULTRAFILTRATION. A REVIEW - Rivas, Bernabe L; Sanchez, Julio; Butter, Bryan (Journal of the Chilean Chemical Society, 2020)
This manuscript is an overview of the versatile biopolymer materials alginic acid, carboxymethyl cellulose, and quaternized chitosan which contain different functional groups to remove hazardous inorganic species. These bioadsorbents are completely water-soluble and have a high versatility to achieve a higher sorption capacity and efficiency under different experimental conditions in combination with ultrafiltration membranes through the liquid-phase polymer-based retention (LPR) technique. In general, these bioadsorbents are more friendly with the environment and have a higher biodegradability compared with those more employed synthetic polymers.